A study on traditional Melaka malay costume for children in Hang Tuah period/ Alin Aqilah Idris - Idris, Alin Aqilah (2019)
The influenced of Traditional Melaka Malay Costume for Children in Hang Tuah period were studied. The aim of the researcher is to analyse and to find out Traditional Melaka Malay Costume in Hang Tuah period of boy and girl for children nowadays. According to the book entitle "Pakaian Melayu Sepanjang Zaman ,. by Abas Alias and Nonnawi. MD Namawi. The evolution of this costume is at the highest peak in the era of Melayu Melaka. It was introduced by Parameswara in 14th century. And in volume 27th in Sejarah Melayu book recorded that a statement is made and fonnally used by Malay today. From a quote is it's been understand that Tun Hassan live through Sultan Mahmud Shah reigned (14881511) has been the pioneer towards Malay clothing renovation at present. Qualitative Method has been used. A variety books were used for this research. An interview has been carried out for people in the age of 20 to 40 years old. They were shown response about agreement of blending illustration in children costume to attract their interest to wear and reasons that effect children awareness toward Traditional Melaka Malay Costume. People were asked ten comprehension questions. Therefore an illustration storybook in Hang Tuah period is produced.